Discovery of hydroxyl 1, 2-diphenylethanamine analogs as potent cholesterol ester transfer protein inhibitors. Issue 14 (15th July 2016) - Jiang, Ji; Finlay, Heather; Johnson, James A.; Harikrishnan, Lalgudi; Kamau, Muthoni; Qiao, Jennifer; Wang, Tammy; Adam, Leonard; Taylor, David; Yang, Richard; Sleph, Paul; Chen, Alice Ye A.; et al.
Graphical abstract: Abstract: Hydroxyl 1, 2-diphenylethanamine analogs were identified as potent inhibitors of cholesterol ester transfer protein (CETP), a therapeutic target to raise HDL cholesterol. In an effort to improve the pharmaceutical properties in the previously disclosed DiPhenylPyridineEthanamine (DPPE) series, polar groups were introduced to the N-linked quaternary center. Optimization of analogues for potency, in vitro liability profile and efficacy led to identification of lead compound16 which demonstrated robust pharmacodynamic effects in human CETP/apo-B100 dual transgenic mice.